Peran Berpikir Intuitif dan Analitis dalam Memecahkan Masalah Matematika - Muniri, Muniri (Institut Agama Islam Negeri (IAIN) Tulungagung, 2018)
Intuition has a big role when the analytic (formal) thinking process does not have the ability to reach it to the problems at hand. The presence of this intuition is spontaneous, immediate and sudden, and sometimes unpredictable. However, its presence is not suddenly but supported by the knowledge and experience, skills and skills possessed, through perceptions and feelings. In this context, intuition serves to facilitate the realm of the mind and makes it easy to understand and solve problems (red mathematical problems) in addition to the role of analytical and formal thinking is also required. Thus, intuition can be a means of opening the gates of ideas or ideas of solution discovery before formal steps are done analytically. The author seeks to illustrate the frameworks of these two forms of thinking (intuitive-analytical) inseparable from one another, but they give benefit from each other in the cycle of mathematical problem-solving.